2008
DOI: 10.1007/s00122-008-0915-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and verification of QTLs for agronomic traits using wild barley introgression lines

Abstract: A set of 39 wild barley introgression lines (hereafter abbreviated with S42ILs) was subjected to a QTL study to verify genetic effects for agronomic traits, previously detected in the BC2DH population S42 (von Korff et al. 2006 in Theor Appl Genet 112:1221-1231) and, in addition, to identify new QTLs and favorable wild barley alleles. Each line within the S42IL set contains a single marker-defined chromosomal introgression from wild barley (Hordeum vulgare ssp. spontaneum), whereas the remaining part of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
59
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 67 publications
(67 reference statements)
10
59
0
Order By: Relevance
“…A third QTL (QHei.S42IL-7H) with an increasing effect of the Hsp allele was detected on chromosome 7H. Here an effect that was already found in the studies of von Korff et al [10], Schmalenbach et al [15] and March et al (in prep.) could be verified.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…A third QTL (QHei.S42IL-7H) with an increasing effect of the Hsp allele was detected on chromosome 7H. Here an effect that was already found in the studies of von Korff et al [10], Schmalenbach et al [15] and March et al (in prep.) could be verified.…”
Section: Discussionsupporting
confidence: 76%
“…March et al (in prep.) and Schmalenbach et al [15] found the same effect in their studies. Von Korff et al [10] found a similar effect in the region where the Hsp introgression of S42IL-109 was mapped.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Early and delayed heading are usually correlated with lesser and more Sdw, respectively (Wang et al, 2010; Arifuzzaman et al, 2014). A dominant early heading allele Ppd-H1 has been reported in wild barley accession ISR42-8 and its effect has been confirmed in introgression lines S42IL-107 harboring ISR42-8 Ppd-H1 allele in Scarlett (spring type) background (Schmalenbach et al, 2009; Arifuzzaman et al, 2014). However, here we identified two unique haplotypes HOR2692 (Iranian wild accession) and NGB4673 (Landrace from Afghanistan) having heterozygous alleles at QTL QSdw.2H.b.…”
Section: Discussionmentioning
confidence: 80%
“…Many studies have demonstrated the value of alleles originating from un-adapted and unimproved germplasm showing that centuries of selective breeding have not necessarily resulted in the accumulation of all the optimal alleles. For example, several barley cultivars have been released in Europe that contain fungal resistance genes introgressed recently from H. spontaneum (von Korff et al 2005;Schmalenbach et al 2009). A major challenge for the future is to streamline this process using high throughput genomics approaches.…”
Section: Introductionmentioning
confidence: 99%